1994
DOI: 10.1007/bf00201661
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of (GACA)n simple repeats in an exceptional 14p+ marker chromosome

Abstract: An inherited 14p+ marker chromosome with an unusually large differentially staining region (DSR) on the short arm was examined with a number of banding techniques and by non-radioactive in situ hybridization using various repetitive DNA probes. The increase in the size of this variant chromosome was 40% that of a normal chromosome 14. The extra chromosomal material in the DSR consisted mainly of GC-rich constitutive heterochromatin within which two equally sized clusters of 18S + 28S ribosomal RNA genes were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
(29 reference statements)
0
8
0
1
Order By: Relevance
“…The chemical similarities to DNA and the relative abundance of RNA in the cytosol, the primary cellular site for MMC activation, make RNA a likely target. That rRNA constitutes ϳ71% of total cellular RNA in eukaryotes and that it contains G/C-rich regions for preferred MMC binding (34) suggest that rRNA is likely the primary cellular RNA target. We propose that MMC rapidly binds 18S rRNA in the cytosol causing degradation and profound decreases in cytosolic levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical similarities to DNA and the relative abundance of RNA in the cytosol, the primary cellular site for MMC activation, make RNA a likely target. That rRNA constitutes ϳ71% of total cellular RNA in eukaryotes and that it contains G/C-rich regions for preferred MMC binding (34) suggest that rRNA is likely the primary cellular RNA target. We propose that MMC rapidly binds 18S rRNA in the cytosol causing degradation and profound decreases in cytosolic levels.…”
Section: Discussionmentioning
confidence: 99%
“…The most abundant RNA species in eukaryotes is rRNA, which is required to form the ribosomal complex and produce all cellular proteins (33). rRNA is also G/C-rich (34), exists in close proximity to the enzymes that activate MMC, and lacks some of the protection afforded to nuclear DNA by membranes and extensive repair mechanisms. It has been noted that there is an increase in ribosome number in tumor cells versus their normal counterparts, further increasing the probability of MMC interacting with rRNA (35).…”
mentioning
confidence: 99%
“…1, bottom, right four images). Schmid et al (1994) have previously reported the amplification of Bkm sequences in a chromosome 14 with an enlarged short arm. In that case, the amplified DNA consisted of (GACA) n repeats.…”
Section: Resultsmentioning
confidence: 99%
“…In the present cases, such selection is not obvious, due to the nature of the amplified elements, and the amplification is thus more puzzling. Amplification into visible elements in the absence of an apparent selective advantage has been reported in the form of enlargements of the short arms of the acrocentric chromosomes (Bernstein et al, 1981;Pérez-Castillo et al, 1986;Schmid et al, 1994). In such cases, the amplified material represented DNA normally present at the particular locus and was rather GC rich.…”
mentioning
confidence: 99%
“…(Csonka et al 2000;Hadlaczky et al 1991;Hadlaczky 2001;Holló et al 1996;Keresö et al 1996;Lindenbaum et al 2004;Praznovszky et al 1991). There is no evidence in humans that amplification of these pericentromeric sequences is deleterious to an individual, as polymorphisms in the short arms of acrocentric chromosomes have been shown to consist of amplified pericentromeric heterochromatin and/or rDNA (Conte et al 1997;Friedrich et al 1996;Sands 1969;Sofuni et al 1980;Stergianou et al 1993;Trask et al 1989A;Trask et al 1989B;Verma et al 1977;Warburton et al, 1976) and have been inherited with no adverse effects (Bernstein et al 1981;Cooper and Hirschhorn 1962;Schmid et al 1994;Therkelsen 1964;Yoder et al 1974). Furthermore, supernumerary chromosomes derived from amplified pericentromeric heterochromatin and/or rDNA sequences of acrocentric chromosomes have been shown to be stably inherited through 1-3 generations in humans without any deleterious effects of phenotypes (Adhvaryu et al 1998;Blennow et al 1994;Brøndum-Nielsen and Mikkelsen 1995;Crolla et al 1997;Hadlaczky et al 2002;Howard-Peebles 1979;Mukerjee and Burdette 1966).…”
Section: Overview Of De Novo Formed Stallite-based Mammalian Artificimentioning
confidence: 99%